The economics of photovoltaic (PV) drip irrigation systems: A case study for India. - Philip, Kimberley A. (University of Ottawa (Canada), 1996)
Agriculture accounts for 50% of India's gross national product and irrigated agriculture for two thirds of the nation's crop output. The energization of agricultural pumpsets is one of the main goals of India's rural electrification program but the economics of these long power line extensions for small power loads are often unfavourable. Other options for satisfying India's need for remote irrigation water supply systems include the use of photovoltaic (PV) pumps. In this study an attempt was made to determine suitable applications for PV pumping systems in the irrigation sector. Drip irrigation was considered the most appropriate method of irrigation for use with a PV pump. Grapes were considered a suitable crop due high water savings under drip irrigation, the perennial nature of the crop, and high economic returns. Insolation, evapotranspiration, and effective precipitation were determined for a number of stations across India. This information was used to calculate irrigation water requirements for grapes and size a suitable PV pumpset. The cost of irrigating with a PV pump was compared to costs for other remote water pumping options and the net present worth of all costs and benefits for grape cultivation were calculated from both an economic and financial perspective. PV pumping systems did not prove to be the least cost option for irrigation due to the exceptionally low cost of diesel pumpsets in India. In spite of this, the net present worth of grape cultivation with a PV drip irrigation system was found tc be positive as was the incremental benefit of PV drip irrigation over surface irrigation with a diesel pump.
Keywords: Engineering, Agricultural.